The development and validation of the irrational beliefs scale for people living with HIV - LongSheng Xie; Min Tian; Wei Wei; JianLan Ren; YuBei Liu; ZhaoLan Yu; YanHua Chen (BMC Public Health)
Abstract Objective To develop a culturally adapted scale measuring HIV-related irrational beliefs among PLHIV in China, and to examine its psychometric properties. Methods The study was conducted from 05/2022 to 11/2023 with four stages. Stage 1: a pool of items was constructed through semi-structured interviews with 48 PLHIV; Stage 2: 14 multidisciplinary experts were invited to evaluate the content validity of the scale; Stage 3: the test-retest reliability of the scale was conducted with 31 PLHIV; and Stage 4: a convenience sampling was used to conduct an online and on-site survey of PLHIV in eight designated institutions of antiretroviral treatment in Luzhou and Anyue regions. Results Finally, a pool of 45 items was formed, with a Scale-level Content Validity Index average was 0.97 and the content validity index for each item was 0.86-1. The intra-class correlation coefficient for test-retest reliability was 0.845. After exploratory factor analysis, four factors were extracted: Self-related Irrational Beliefs (SRIBs); Disease-related Irrational Beliefs (DRIBs); Treatment-related Irrational Beliefs (TRIBs), and Privacy-related Irrational Beliefs (PRIBs), with a total of 35 items, which could explain 60.6% variance. The Cronbach’s α of the Irrational Beliefs Scale of PLHIV was 0.951, and the Cronbach’s α of each dimension ranged from 0.851 to 0.928. Conclusion The scale could be used as a valid tool for measuring irrational beliefs among PLHIV.